A history of Ottoman architecture - Freely, John.; Baker, Anthony E. (Southampton ; Boston : WIT Press, 2010)
This text is focused on the history of the extant buildings in the Republic of Turkey. The book begins with a brief history of the Ottoman Empire and develops by outlining the mains features of Ottoman architecture and discusses the biography of the great Ottoman architect Sinan.
Includes bibliographical references (p. 435-437).
Keywords: Architecture, Ottoman; Architecture -- Turkey -- History; Islamic architecture -- Turkey; Turkey -- History -- Ottoman Empire, 1288-1918.